Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Karyawan di Koperasi Jasa Multi Pihak Mitra Jenggala Sejahtera Desa Ketenger - Monika, Isna; Kiswoyo, Kiswoyo (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study aims to analyze the influence of motivation and work discipline on employee performance and identify indicators that influence these variables at the Mitra Jenggala Sejahtera Multi-Party Service Cooperative, Ketenger Village. The independent variables in this study are motivation and work discipline, while the dependent variable is employee performance. This study uses a census technique, where the entire population consisting of 66 cooperative employees is sampled. Data analysis was carried out using multiple linear regression, which includes the t-test and F-test. Previously, the data were tested with validity, reliability, descriptive statistics, and classical assumption tests, which include multicollinearity, heteroscedasticity, and normality tests. Data processing was carried out with the help of the SPSS program. The results of the study indicate that motivation has a significant influence on employee performance. Likewise, work discipline has also been shown to have a significant effect on employee performance. These findings indicate that increasing motivation and work discipline can increase employee productivity and performance at the Mitra Jenggala Sejahtera Multi-Party Service Cooperative.